Transforming Lives: The Positive Impact of School Retention Strategies on the Probability of Students’ Dropout in Medellin - Andres Camacho Murillo; Natalia Arango Ramírez (Revista de Economía del Rosario)
This study assesses the causal effect of school retention strategies on the probability of school dropout in Medellin, Colombia. The probit model is estimated using microdata on enrollment published by the Ministry of National Education and data on beneficiaries of school retention programs, year 2019. Three impact evaluation methods are employed to obtain the counterfactual group of each school retention program: Self- Selected Comparisons, Propensity Score Matching, and Endogenous Treatment-Effects. Results from the latter method show that the probability of school dropout is lower for students enrolled in the School Meals Program, School Transportation Program, or Complementary School Day Program, compared to the counterfactual groups, by -1.0 pp, -3.17 pp, and -2.97 pp, respectively. However, the study finds heterogeneous effects around school retention programs, which are explained by students’ social class, nationality, and sex.